Communication as the Lifeblood of Islamic Educational Organizations: A Systems and Sensemaking Perspective - Yudo Handoko; Martinis Yamin; Minnah El Widdah; Nurul Huda (Yayasan Adra Karima Hubbi, 2026)
Background. Educational organizations increasingly operate within complex and dynamic environments that demand not only effectiveness but also long-term organizational sustainability. Despite this condition, communication in educational institutions is often treated instrumentally as a managerial tool, rather than as a constitutive process that sustains organizational coherence, learning, and ethical legitimacy. This limitation is particularly evident in Islamic educational organizations, where bureaucratic structures, cultural hierarchies, and normative values intersect. Purpose. This article aims to reconceptualize communication as the lifeblood of Islamic educational organizations by integrating systems theory and sensemaking theory. It seeks to provide a theoretical framework that positions communication as a central sustainability mechanism enabling organizational integration, adaptive capacity, and meaning construction. Method. This study employs a conceptual and theoretical analysis through critical synthesis of systems theory, organizational sensemaking theory, and Islamic communication ethics. Relevant literature from organizational communication, educational leadership, and Islamic education studies is systematically examined to develop an integrative conceptual framework. Results. The analysis demonstrates that communication functions as the primary integrative flow connecting organizational subsystems, facilitating feedback loops, and enabling collective sensemaking. Within Islamic educational organizations, communicative principles such as shura (consultative deliberation), amanah (trust and responsibility), and an-na???ah (ethical counsel) operate as ethical sensemaking practices that strengthen organizational coherence and sustainability. Conclusion. The analysis shows that communication functions as a key integrative flow connecting organizational subsystems, facilitating feedback, and enabling collective sensemaking. In Islamic educational organizations, communicative principles such as shura (deliberation), amanah (trust and responsibility), and an-na???ah (ethical advice) operate as ethical sensemaking practices that strengthen organizational coherence and sustainability.